Experiencing and Feeling Light Through Peter Zumthor's Architectural Works - Suwandy Halim; Agus Suharjono Ekomadyo (Universitas Bandar Lampung (UBL), 2022)
Architecture is closely related to the experience of space that affects the behavior, feelings, and experiences of its users. When designing, architects can explore and engineer existing elements to enrich the space experience so that the designed building can interact and have an impact with its users. Peter Zumthor is one of the architects who is deeply immersed in the experience of space through the lighting produced when designing. Based on this, several designs by Peter Zumthor will be studied such as the Saint Benedict Chapel, Therme Vals, Kunsthaus Bregenz and Brother Klaus as case examples. This research was conducted using the theoretical framework of Poethics of Architecture: Theory of Design by Antony. C. Anthoniades, namely Tangible and InTangible Channel, which aims to explain the way architect Peter Zumthor in realizing his architecture through lighting engineering in order to realize the desire for experience that is raised in his design. It was found that Peter Zumthor took many approaches through lighting such as fantasy, metaphor, obscure, geometry, material and nature in each of his designs. Thus, it is concluded that Peter Zumthor conducts many negotiations and interpretations in these six aspects to produce an architectural work that has an impact on the feelings and experiences of each user.